2018
DOI: 10.7759/cureus.2400
|View full text |Cite
|
Sign up to set email alerts
|

Urgent Anterior Cervical Osteophytectomy for an Asymptomatic Cervical Hyperostosis to Overcome Failed Intubation

Abstract: Cervical spondylosis and ankylosing hyperostosis of the cervical vertebrae are usually asymptomatic. This is a case report of a patient with massive anterior cervical osteophytes resulting in failure of intubation prior to a lumbar canal stenosis surgery. The osteophytes extended from C3 to C7 and resulted in the anterior displacement of the pharynx and the trachea. The patient was managed successfully with anterior cervical osteophytectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…We have reviewed 67 studies reported in the literature of the past 25 years, which include patients with symptomatic ACOs treated by this approach. [ 11 12 13 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 ] Nineteen studies[ 29 30 34 38 39 49 50 51 54 56 62 …”
Section: Discussionmentioning
confidence: 99%
“…We have reviewed 67 studies reported in the literature of the past 25 years, which include patients with symptomatic ACOs treated by this approach. [ 11 12 13 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 66 67 68 69 70 71 72 73 74 75 76 77 78 79 80 ] Nineteen studies[ 29 30 34 38 39 49 50 51 54 56 62 …”
Section: Discussionmentioning
confidence: 99%
“…It is indicated in case of failure of conservative management, increased dysphagia with important weight loss and upper airway obstruction. It is performed via the anterior (Smith-Robinson approach) and trans pharyngeal approaches [5, 10-12]. The resection of the osteophytes is performed by creating a long incision with adequate exposure.…”
Section: Discussionmentioning
confidence: 99%